Income Analysis in Perspective of Competitive Advantage of Ornamental Plant Traders During a Pandemic in Lamongan District - Eka Martha Yuliatin; Anita Handayani (Universitas Muhammadiyah Gresik, 2022)
This research aims to analyze income in the perspective of competitive advantage for ornamental plant traders in Lamongan District, where ornamental business actors try to maintain business income and so that there is no increase during a pandemic when competition between traders is intense. The research method used in this research is a qualitative descriptive approach. By collecting data from 6 informants and 1 key informant as a research opener in order to get accurate results. The results of income analysis research in the perspective of competitive advantage for ornamental plant traders during a pandemic in Lamongan District, the welfare of ornamental plant traders in Lamongan District is caused by actors and actors as well as customer satisfaction factors so that during the pandemic it does not make the business out of business and remains visited by customers by using a competitive advantage strategy, this study shows that the longer the business, the more income received. Keywords: Income; Competitive Advantage Perspective; Ornamental Plants; Trader; Pandemic;